Zabytek nieruchomy a dziedzictwo architektoniczne. Uwagi w związku z ratyfikacją Konwencji o ochronie dziedzictwa architektonicznego Europy - Jankowska-Sabat, Monika (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The article examines the concept of architectural heritage in the context of the Council of Europe’s Convention of 3 October 1985 on the Protection of the Architectural Heritage of Europe, ratified by Poland in 2011. The first part of the article explains the origins of the word “monument” and how it evolved in successive Polish legal acts. Part two deals with the origins and evolution of the legal concept of architectural heritage. The final part indicates differences between the Polish cultural heritage protection law and the provisions of the Convention.
Keywords: zabytki nieruchome; dziedzictwo architektoniczne; konwencja o ochronie dziedzictwa architektonicznego Europy; ratyfikacja